SOLUTION OF THE REVERSE FLOW REACTOR MODEL USING HOMOTOPY ANALYSIS METHOD - Suharsono, Suharsono; Wulandari, Sri; Nuryaman, Aang; Usman, Mustofa; Wamiliana, Wamiliana; Daoud, Jamal (IIUM Engineering Journal, 2020)
Methane (CH4) is one of the most dangerous greenhouse gases in the atmosphere. A reverse flow reactor is utilized to convert CH4 to carbon dioxide (CO2) as a means of reducing the effect of global warming. The dynamics of its dependent variables can be stated by a set of convective-diffusion equations. In this article, we examined analytical solutions of temperature dynamics and methane conversion for a 1-D pseudo homogeneous model without refrigeration by using the homotopy analysis method. The results show that temperature and conversion of methane will go to constant when time goes to infinity. ABSTRAK: Metana (CH4) merupakan salah satu gas rumah hijau paling berbahaya di atmosfera. Reaktor aliran balik telah dipakai bagi menukar CH4 kepada CO2 bagi mengurangkan kesan pemanasan global. Dinamik pemboleh ubah bersandar ini dapat diterangkan melalui satu set persamaan konvektif-difusi. Artikel ini akan mengkaji penyelesaian analisis dinamik suhu dan penukaran metana bagi model 1-D pseudo-homogen tanpa penyejukan dengan menggunakan kaedah analisis homotopi. Hasil kajian menunjukkan bahawa suhu dan penukaran metana akan berterusan dengan masa tak terhingga.